2020
DOI: 10.1002/jeq2.20112
|View full text |Cite
|
Sign up to set email alerts
|

Dietary composition and particle size effects on swine manure characteristics and gas emissions

Abstract: Nutrients excreted from animals affect the nutritive value of manure as a soil amendment as well as the composition of gases emitted from manure storage facilities. There is a dearth of information, however, on how diet type in combination with dietary particle size affects nutrients deposited into manure storage facilities and how this affects manure composition and gas emissions. To fill this knowledge gap, an animal feeding trial was performed to evaluate potential interactive effects between feed particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Results from these studies have shown low NUE (30 to 43%) based on the amount of N retained as a percentage of total dietary N consumed. These N-flow values are supported by data conducted using an animal metabolism crate manure storage system designed to simulate manure storage conditions in typical swine facilities (Trabue and Kerr, 2014;Kerr et al, 2018;Trabue et al, 2019a;Trabue et al, 2019b;Kerr et al, 2020;Trabue et al, 2021a;Trabue et al, 2021b;Trabue et al, 2022). In these studies, calculated mass balance of N did not, however, account for all of the consumed N, with these researchers speculating that the difference may be due to ammonia losses from metabolism crates and flooring surfaces during the fecal and urine collection process which has been shown to represent 19 to 25% of the N consumed (Burton and Beauchamp, 1986;van Kempen et al, 2003;Li et al, 2011;Costa, 2017).…”
Section: Dietary N Balancementioning
confidence: 79%
See 2 more Smart Citations
“…Results from these studies have shown low NUE (30 to 43%) based on the amount of N retained as a percentage of total dietary N consumed. These N-flow values are supported by data conducted using an animal metabolism crate manure storage system designed to simulate manure storage conditions in typical swine facilities (Trabue and Kerr, 2014;Kerr et al, 2018;Trabue et al, 2019a;Trabue et al, 2019b;Kerr et al, 2020;Trabue et al, 2021a;Trabue et al, 2021b;Trabue et al, 2022). In these studies, calculated mass balance of N did not, however, account for all of the consumed N, with these researchers speculating that the difference may be due to ammonia losses from metabolism crates and flooring surfaces during the fecal and urine collection process which has been shown to represent 19 to 25% of the N consumed (Burton and Beauchamp, 1986;van Kempen et al, 2003;Li et al, 2011;Costa, 2017).…”
Section: Dietary N Balancementioning
confidence: 79%
“…In a similar and inconsistent manner, pigs fed diets containing increased dietary fiber have shown an increase (Velthof et al, 2005;Jarret et al, 2011a;Jarret et al, 2011b;Li et al, 2011) or no change (Kerr et al, 2006) in CH 4 emissions; decreased (Kerr et al, 2006) or no effect (Li et al, 2011) on N 2 O emissions; and no effect on CO 2 emissions (Li et al, 2011). Lastly, Trabue and Kerr (2014); Kerr et al (2020), andTrabue et al (2022) reported no effect of feeding high dietary fiber diets on CO 2 , CH 4 , or N 2 O emissions. Therefore, within the production facility, diet composition differences have dramatic effects on N excretion and NH 3 emissions, but limited and inconsistent effects on GHG emissions.…”
Section: Nitrogen Excretion and Emissionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Accordingly, it was the aim of this study to investigate for the first time the effect of selected pure chemicals, representing relevant constituents of manure [ 41 , 42 , 43 , 44 , 45 ], on the soil sorption of PhACs. This was done by using urea and potassium dihydrogen phosphate (KH 2 PO 4 ) as major nutrient components, acetic acid and phenol as representatives of volatile organic compounds, and nonadecanoic acid (C:19) as a non-polar organic constituent of manure.…”
Section: Introductionmentioning
confidence: 99%
“…In aerobic conditions, manure will undergo mineralization in which microbes reduce the organic materials into inorganic matter (i.e., nitrogen, potassium, and phosphorus) that are essential for plant nutrients. When manure is present in anaerobic conditions, fermentation will result in the breakdown of glucose (Kerr et al, 2020). The change of pH in the feces can cause CO2, methane, and ammonia to be produced (Dai et al, 2015).…”
Section: Manure Managementmentioning
confidence: 99%